Impact of different factor VIII inhibitor kinetic profiles on the inhibitor titer quantification using the modified Nijmegen–Bethesda assay. Issue 8 (12th December 2022) - Ketteler, Carolin; Hoffmann, Ingrid; Davidson, Simon; Chen, David; Tiede, Andreas; Richter, Nina
Abstract: Background: Coagulation factor VIII (FVIII) inhibitor titer quantification is vital for optimizing care in people with hemophilia A. Objectives: This study analyzed the impact of the different kinetic profiles of four FVIII monoclonal antibodies on inhibitor titer quantification using the modified Nijmegen–Bethesda assay. Methods: Concentration‐related and time‐related profiles of FVIII antibodies (4A4, BO2C11, 2‐54, ESH‐8) were evaluated in vitro. FVIII residual activity was measured using a one‐stage clotting assay and chromogenic substrate assay. Profiles of the FVIII antibodies were compared with the theoretical kinetic model: the ideal log (residual activity)‐linear (inhibitor concentration) relationship. Different theoretical kinetic model–dependent and –independent criteria to calculate FVIII inhibitor titer were compared. Results: Factor VIII monoclonal antibodies had different concentration‐related and time‐related profiles, ideal for comparative analysis using the modified Nijmegen–Bethesda assay. The kinetic profile of 4A4 was similar to the theoretical kinetic model, while BO2C11 showed a steeper curve, and 2‐54 and ESH‐8 a flatter curve, than the model. In the modified Nijmegen–Bethesda assay, conversion of measured FVIII residual activities for different inhibitor dilutions into FVIII inhibitor titer is based on the theoretical kinetic model. Therefore, titer calculations for FVIII inhibitors that deviate from the model are prone to underestimation or overestimation. Calculating a theoretical dilution at 50% FVIII residual activity by sigmoidal regression reflecting different kinetic inhibition profiles can provide a more accurate titer result. Conclusion: Kinetic profiles of FVIII antibodies can deviate from the theoretical kinetic model in the modified Nijmegen–Bethesda assay, leading to differences in FVIII inhibitor titer quantification. Abstract :